Analisis Perbandingan Return dan Risiko Saham LQ45 dan Saham Non LQ45 - Kasmawati Laturauw; Erna Garnia (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This study provides evidence of a comparative analysis of returns and risks between LQ45 shares and non-LQ45 stock. This study explains that the LQ45 and non-LQ45 stock groups have different liquidity. This study uses two variables which are seen in terms of return and risk. This research method uses descriptive and comparative test. This study uses montly stock data from 2013 to 2017. The results oh the study show that there is no difference in returns between LQ45 shares and non LQ45 shares. In contrast to risk, where the results show that there are differences in risk between LQ45 shares and non-LQ45 shares